Reverse hybrid therapy achieves a similar eradication rate as standard hybrid therapy for Helicobacter pylori infection. Issue 3 (March 2020) - Lin, Te-Fu; Wu, Deng-Chyang; Tsay, Feng-Woei; Tsai, Kuo-Wang; Tsai, Tzung-Jiun; Peng, Nan-Jing; Kao, Sung-Shuo; Chen, Wen-Chi; Chen, Yan-Hua; Hsu, Ping-I
Abstract : Background: Reverse hybrid therapy is a simplified hybrid treatment for Helicobacter pylori infection. It achieves a higher eradication rate than standard triple therapy. This study aimed to compare the efficacies of reverse hybrid and hybrid therapies in the treatment of H. pylori infection. Methods: From September 2008 to September 2017, 490 H. pylori -infected patients who received 14 days of reverse hybrid therapy (proton pump inhibitor plus amoxicillin for 14 days and clarithromycin plus metronidazole for the initial 7 days; n = 252) or hybrid therapy (proton pump inhibitor plus amoxicillin for 14 days and clarithromycin plus metronidazole for the final 7 days; n = 238) were included in this retrospective cohort study. Helicobacter pylori status was examined 6–8 weeks after therapy. Results: The eradication rates of the reverse hybrid and hybrid therapies by modified intention-to-treat analysis were comparable (96.4% vs 96.6%; p = 0.899). There were no differences in the efficacy of eradication between therapies for clarithromycin-resistant strains (87.0% vs 90.0%) or metronidazole-resistant strains (97.7% vs 100.0%). In addition, there were comparable frequencies of adverse events for both treatments (18.7% vs 13.0%) and treatment adherence (94.4% vs 97.1%). Conclusion: Reverse hybrid therapy can achieve a similar eradication rate to hybrid therapy for H. pylori infection.